COMMUNICATION BETWEEN THE MUSCULOCUTANEOUS AND MEDIAN NERVE: OCCURRENCE ON BOTH SIDES - K., Remya; Krishnamurthy, Ashwin; K., Kavitha (Journal of Health and Allied Sciences NU, 2011)
Communications between musculocutaneous nerve and median nerve may be of considerable significance to neurologists and orthopaedicians when dealing with patients of nerve entrapment syndromes of the upper limb. Many authors have mentioned about an occurrence of such a variation previously, but the presence of a communication between the two nerves in both the arms has not been cited to the best of our knowledge. During routine dissection on a 72 year old male cadaver for the under graduate students in the Department of Anatomy at K.S. Hegde Medical Academy, we encountered an anomalous communication between musculocutaneous and median nerve in both the upper limbs. The communicating branch arose from the musculocutaneous nerve at a distance of 12.6 cm and 12.5 cm from the tip of coracoid process on right and left side and joined the median nerve 16.2 cm from the same bony point. Communications between nerves like this may explain abnormal debilities in certain cases of trauma of the upper arm. Lack of awareness of such variations with different patterns of communications between musculocutaneous and median nerve might complicate surgical repair of the nerves.